2019
DOI: 10.1136/jclinpath-2019-206109
|View full text |Cite
|
Sign up to set email alerts
|

The Paris System for reporting urinary cytology in daily practice with emphasis on ancillary testing by multiprobe FISH

Abstract: AimsThe Paris System (TPS) was introduced in the diagnostic routine with the goal to simplify and standardise diagnostic reporting of urinary cytology. The diagnostic categories of TPS are based on defined cytological criteria, with a focus on high-grade urothelial carcinoma (HGUC). While the categories ‘negative for HGUC (NHGUC)’ and ‘HGUC’ are straightforward, the categories ‘atypical urothelial cells (AUC)’ and ‘suspicious of HGUC (SHGUC)’ remain inconclusive. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
2
8
1
2
Order By: Relevance
“…Our study demonstrated a significantly improved association of AUC with positive FISH results, as 38% of AUC had a positive FISH result in the post‐TPS period compared with 17% in the pre‐TPS period. Vlajnic and colleagues reported a similar association of 44% AUC having positive FISH results when using TPS 23 . These studies support the finding that FISH may further improve risk stratification in AUC in the TPS era.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our study demonstrated a significantly improved association of AUC with positive FISH results, as 38% of AUC had a positive FISH result in the post‐TPS period compared with 17% in the pre‐TPS period. Vlajnic and colleagues reported a similar association of 44% AUC having positive FISH results when using TPS 23 . These studies support the finding that FISH may further improve risk stratification in AUC in the TPS era.…”
Section: Discussionsupporting
confidence: 52%
“…The improved performance for AUC was also reflected in the cytology‐UroVysion correlation. UroVysion is a US Food and Drug Administration‐approved test to detect aneuploidy in chromosomes 3, 7, and 17 and loss of the 9p21 locus using FISH in urine specimens, which is considered a useful adjunct for urinary cytology, especially with an AUC diagnosis 23,24 . Our study demonstrated a significantly improved association of AUC with positive FISH results, as 38% of AUC had a positive FISH result in the post‐TPS period compared with 17% in the pre‐TPS period.…”
Section: Discussionmentioning
confidence: 67%
“…The ROHM ranged from 13.04% (95% CI, 0.0932; 0.1796) for the NHGUC to 91.79% (95% CI, 0.8722; 0.9482) for the HGUC and other malignancies. Notably, the ROHM for the AUC category was calculated at 38.65% (95% CI, 0.3042; 0.4759), prompting a close follow-up and potential ancillary testing with FISH or other modalities, such as UroSEEK, to better stratify such cases [1,9,56,57]. One reason why the ROHM of the SHGUC and HGUC categories was not closer to 100% could be the tendency of cytopathologists to overestimate the N/C ratio, as has been reported in the literature [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…It comprises seven diagnostic categories: nondiagnostic, negative for high-grade urothelial carcinoma (NHGUC), atypical urothelial cells (AUC), suspicious for high-grade urothelial carcinoma (SHGUC), HGUC, low-grade urothelial neoplasm (LGUN), and other primary or secondary malignancies [7]. TPS also supports the use of ancillary techniques (e.g., UroVysion FISH) for indeterminate interpretations [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…This creates a situation in which these ancillary tests appear to outperform urinary cytology because these tests detect LGUCs that are otherwise classified into the “Negative” category according to TPS. For this reason, the overall interpretation of ancillary test results together with TPS diagnoses should be made with caution 43 . Furthermore, UroVysion may be impractical for many labs to order because samples must be less than 72 h old from the time of collection, which means that performing this test as a reflex is difficult unless there are enough urine specimens to justify performing the test in‐house on a daily basis.…”
Section: Atypical Findings In Clinical Contextmentioning
confidence: 99%